AFGHANISTAN’S POLITICAL SYSTEM: INTERNATIONAL EFFORTS, INTERNAL RESOURCES, AND UNTAPPED RESERVES - ERGASHEV, Bahodyr (CENTRAL ASIA AND THE CAUCASUS, 2011)
A democratic political system is the key to Afghanistan’s future prosperity. The world community is convinced of this, while the already achieved legitimization and democratization of power in this country have inspired its neighbors, the Arab Spring countries, and the Muslim East as a whole. However, the Taliban and its abettors in other countries and other more civilized forces (acting on the sly or even openly) are determined to block the road to progress. The main parameters of the political process in Afghanistan were outlined and accepted as a guide to action ten years ago: a new constitution; a state ruled by law; efficient institutions of state governance; a civil society and political parties as one of its elements; human rights; and a Road Map to free elections. A stronger political system has remained on the agenda of several consecutive international conferences in Bonn (2001); Berlin (2004); London (2006 and 2010), Rome (2007), Paris (2008), Moscow (2009) and The Hague (2009). It is not easy to study the country’s political system during the transition period, identify its context, pinpoint its problems, and outline its prospects. It is much easier to dissect the entire structure of state power (in fact, today the term “political system” looks a bit conservative), which cannot be done in the case of Afghanistan because of the ever-widening involvement of non-state civil institutions in politics. In short, we should take into account all the entities of Afghan politics. The Islamic Republic of Afghanistan has supplied the expert community with a unique target of integrated studies. I have in mind three fairly “widely spaced” components: (1) The relations between the International Security Assistance Force — ISAF members, Russia, China, India, Pakistan, the Soviet successor states in Central Asia, etc. (2) The country’s own past and present. (3) Its development prospects.